Ni-catalyzed alpha-alkylation of unactivated amides and esters with alcohols by hydrogen auto-transfer strategy - Midya, Siba P.; Rana, Jagannath; Pitchaimani, Jayaraman; Nandakumar, Avanashiappan; Madhu, Vedichi; Balaraman, Ekambaram (CHEMSUSCHEM, 2018)
A transition-metal-catalyzed borrowing hydrogen/hydrogen auto-transfer strategy allows the utilization of feedstock alcohols as an alkylating partner, which avoids the formation of stoichiometric salt waste and enables a direct and benign approach for the construction of C-N and C-C bonds. In this study, a nickel-catalyzed alpha-alkylation of unactivated amides and ester (tert-butyl acetate) is carried out by using primary alcohols under mild conditions. This C-C bond-forming reaction is catalyzed by a new, molecularly defined nickel(II) NNN-pincer complex (0.1-1 mol %) and proceeds through hydrogen auto-transfer, thereby releasing water as the sole byproduct. In addition, N-alkylation of cyclic amides under Ni-catalytic conditions is demonstrated.